P52 A baseline review of the activity of the PICU pharmacists using electronically captured data. Issue 9 (19th August 2020) - Semple, Diarmaid; Brereton, Erika; Dawkins, Ian
Abstract : Aim: To date there are no metrics for the clinical pharmacist service to PICU. It is accepted that use of a Clinical Information Management System (CIMS) has a role in medication safety, 1 however there are few studies that review the information potential of a CIMS for collecting pharmacist activity. 2 Method: Additional fields and custom reports were configured in the CIMS to enable PICU pharmacists to record their activity in the following areas: Medicines reconciliation within 72 hours of admission to PICU Discharge kardex review Analgesia and sedation (A&S) review Clinical pharmacy review Other interventions & medication error reporting continued as per normal practice. Data was analysed using Microsoft Excel®. Results: Complete data was available from July 2017 to end of 2018. There were 1274 medicines reconciliations by a pharmacist within 72 hours of admission (78% admissions). 14% of discharge kardexes had been reviewed prior to discharge to the ward. There was an average of 190 pharmacy reviews per 100 bed days. A total of 780 Pharmacist A&S Plans were documented by the clinical pharmacists – an average of 2 per working day, and 48% of admissions. Comparisons between each six month period showed a significant increase in the number of pharmacists medicines reconciliations (p<0.001). No other differences were found. Conclusion: This study has shown that electronic tracking of pharmacist ward activity is possible. It has the potential to demonstrate compliance with external or internal standards and audits. This data continues to be collected, and therefore these results will be used as a baseline to compare future activity. The findings of this study may encourage other units to replicate, providing data that can be used for comparison. Further configuration of the CIMS to capture other metrics such as TDM, and document discrepancies in medicines reconciliation is planned. References: Forni A, Chu H, Fanikos J. Technology Utilization to Prevent Medication Errors. Current Drug Safety . 2010;5 :13–18. Nelson S, Poikonen J, Reese T, El Halta D, Weir C. The pharmacist and the EHR. Journal of the American Medical Informatics Association . 2016;24 :193–197. Health and Information Quality Authority. Guidance for health and social care providers; Principles of good practice in medication reconciliation. Dublin: HIQA; 2014